2019
DOI: 10.1136/bmjdrc-2019-000696
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral remote temperature monitoring to predict future ulceration for the diabetic foot in remission

Abstract: ObjectiveDaily remote foot temperature monitoring is an evidence-based preventive practice for patients at risk for diabetic foot complications. Unfortunately, the conventional approach requires comparison of temperatures between contralaterally matched anatomy, limiting practice in high-risk cohorts such as patients with a wound to one foot and those with proximal lower extremity amputation (LEA). We developed and assessed a novel approach for monitoring of a single foot for the prevention and early detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…41 Similarly, measures of metabolic control, like HbA 1c , ankle brachial index for perfusion or skin temperature for inflammation are correlated with wound healing but not yet documented routinely in our data. 25,36,42 Conversely, we have no evidence that increasing the complexity of the model structure will raise predictive accuracy. We tested several interaction effects with only marginal improvement in the AUC.…”
Section: Discussionmentioning
confidence: 71%
“…41 Similarly, measures of metabolic control, like HbA 1c , ankle brachial index for perfusion or skin temperature for inflammation are correlated with wound healing but not yet documented routinely in our data. 25,36,42 Conversely, we have no evidence that increasing the complexity of the model structure will raise predictive accuracy. We tested several interaction effects with only marginal improvement in the AUC.…”
Section: Discussionmentioning
confidence: 71%
“…Ideally, practice should begin during treatment to prepare and set expectations for the patient as well as to establish daily routines to maximize adherence to the monitoring regimen post-healing. Fortunately, investigators have recently published a unilateral foot temperature monitoring protocol for the mat that allows patients being treated for a wound on one foot to monitor the unwounded foot [13]. While previous foot temperature monitoring protocols required two feet for contralateral comparison, this new approach requires only one foot, allowing foot temperature monitoring to begin during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that a temperature difference between identical sites on opposite feet of >2.2 • C (equivalent to~4 • F) on two consecutive days can accurately predict ulcer development [21,22]. It has recently been reported that the difference between the median of temperature at six key locations on one foot (the hallux, first, third and fifth metatarsal heads, the mid-foot and heel) and ambient temperature is also able to predict foot ulcer development with an excellent sensitivity, although with limited specificity [23]. This potentially allows people with a unilateral foot ulcer and those with prior unilateral major amputation to also be monitored for the hot spots that are predictive of impending ulcers.…”
Section: Monitoring Foot Temperaturementioning
confidence: 99%
“…The previous trials testing home foot temperature monitoring [17][18][19] have excluded people with peripheral artery disease (PAD), which is an established risk factor for foot ulceration, thereby limiting the generalizability [20][21][22]. Both PAD and DPN have been reported to influence foot temperature [23]. In a recent thermal imaging study, participants with PAD had a significantly higher foot temperature than those that did not have PAD [26,27].…”
Section: Monitoring Foot Temperaturementioning
confidence: 99%
See 1 more Smart Citation